A theory-informed, process-oriented Resident Scholarship Program. Issue 1 (1st January 2016) - Thammasitboon, Satid; Darby, John B.; Hair, Amy B.; Rose, Karen M.; Ward, Mark A.; Turner, Teri L.; Balmer, Dorene F.
Abstract : Background: The Accreditation Council for Graduate Medical Education requires residency programs to provide curricula for residents to engage in scholarly activities but does not specify particular guidelines for instruction. We propose a Resident Scholarship Program that is framed by the self-determination theory (SDT) and emphasize the process of scholarly activity versus a scholarly product. Methods: The authors report on their longitudinal Resident Scholarship Program, which aimed to support psychological needs central to SDT: autonomy, competence, and relatedness. By addressing those needs in program aims and program components, the program may foster residents' intrinsic motivation to learn and to engage in scholarly activity. To this end, residents' engagement in scholarly processes, and changes in perceived autonomy, competence, and relatedness were assessed. Results: Residents engaged in a range of scholarly projects and expressed positive regard for the program. Compared to before residency, residents felt more confident in the process of scholarly activity, as determined by changes in increased perceived autonomy, competence, and relatedness. Scholarly products were accomplished in return for a focus on scholarly process. Conclusions: Based on our experience, and in line with the SDT, supporting residents' autonomy, competence, and relatedness through a process-oriented scholarship program may foster the curiosity, inquisitiveness, and internal motivation to learn that drives scholarly activity and ultimately the production of scholarly products.